Profile of John P. Smol - Sarah C. P. Williams (Proceedings of the National Academy of Sciences, 2026)
John P. Smol has spent more than four decades demonstrating how lake sediment cores can reveal environmental changes spanning decades to centuries. His pioneering work established paleolimnology as a credible scientific discipline, first, by documenting the impact of acid rain on North American lakes in the 1980s and, later, by tracking Arctic climate warming. Through continuous monitoring of High Arctic ponds and lakes, Smol has shown how ice cover duration influences aquatic ecosystems. His recent research reveals that even the deepest Arctic lakes are now crossing ecological thresholds due to accelerated warming, with implications for Indigenous fisheries and northern communities.